2015
DOI: 10.3168/jds.2014-7500
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: The use of a sonomicrometry system for monitoring uterine involution in postpartum dairy cows

Abstract: Sonomicrometry allows the measurement of the distance between 2 piezoelectric crystals and has been widely used to investigate the contractility of the heart and gastrointestinal tract. The objective of this study was to determine whether this method can be used to quantify the reduction in uterine size in cows postpartum. Seven healthy pluriparous Holstein Friesian cows (3.7±0.7 yr old, parity 2.4±0.5, mean±SD) were used. Three weeks before calving, 4 piezoelectric crystals were implanted via laparotomy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The sonomicrometry system (Sonometrics, London, ON, Canada), the surgery for implantation of the piezoelectric crystals and the sonometric measurements and analysis have been described in detail [ 25 ]. In brief, the sonomicrometry system consisted of 4 piezoelectric crystals connected to a sonomicrometer (TRX8), a channel selector box and a Sonometrics data acquisition computer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sonomicrometry system (Sonometrics, London, ON, Canada), the surgery for implantation of the piezoelectric crystals and the sonometric measurements and analysis have been described in detail [ 25 ]. In brief, the sonomicrometry system consisted of 4 piezoelectric crystals connected to a sonomicrometer (TRX8), a channel selector box and a Sonometrics data acquisition computer.…”
Section: Methodsmentioning
confidence: 99%
“…Sonomicrometry has been used experimentally for continuous measurement of cardiac and skeletal muscle contractility [ 22 , 23 , 24 ], and a technique using sonomicrometry was recently established to examine reduction of uterine size in dairy cows. In a study involving seven Holstein Friesian cows, sonomicrometry was found to be suitable for assessment of the reduction in uterine length in the puerperium, and currently, it is the only practical technique available for this purpose [ 25 ].…”
mentioning
confidence: 99%